UPAYA GURU DALAM MENINGKATKAN KREATIVITAS PEMBELAJARAN TEMATIK PADA MASA PANDEMI COVID-19 - Anggita Agustina; Anwar Sa’dullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
In the current pandemic, many teachers find it difficult to develop their creativity, thus making these teachers present learning only through whatsapp media which makes students feel bored and bored. This study aims to answer the questions: 1) What is the form of teacher creativity in thematic learning during the pandemic at MI Islamiyah Kebonsari, 2) What are the factors that hinder and support teacher creativity in thematic learning during the pandemic at MI Islamiyah Kebonsari. The research location is MI Islamiyah Kebonsari Sukun Malang City.“The approach used is qualitative with”descriptive research, with